Sarcopenia is highly prevalent in patients undergoing surgery for gastric cancer but not associated with worse outcomes. Issue 4 (31st August 2015) - Tegels, Juul J.W.; van Vugt, Jeroen L.A.; Reisinger, Kostan W.; Hulsewé, Karel W.E.; Hoofwijk, Anton G.M.; Derikx, Joep P.M.; Stoot, Jan H.M.B.
<x xml:space="preserve">Abstract</x> Objectives Aim of this study was to assess the prevalence of sarcopenia and body composition (i.e., subcutaneous and visceral fat) in gastric cancer surgical patients and its association with adverse postoperative outcome. Methods Preoperative CT scans were obtained from all patients who underwent surgery for gastric adenocarcinoma between January 2005 and September 2012. Total muscle and adipose tissue cross‐sectional area were measured at the level of the third lumbar vertebra (L3) transverse processes. Sarcopenia was defined according to gender‐ and body mass index (BMI)‐specific cutoff points. Primary outcome was in‐hospital mortality. Secondary outcomes were severe postoperative complications (i.e., Clavien–Dindo classification ≥3a complications) and 6‐month mortality. Results In 152 out of a total of 180 (84.4%) patients, a CT‐scan was available for analysis. In total, 86 (57.7%) of the patients were classified as sarcopenic. Sarcopenia was no predictor for in‐hospital mortality (P = 0.52), severe complications (P = 1.00) or 6‐month mortality (P = 0.69). Intraabdominal and subcutaneous adipose tissue measurements were not associated with in‐hospital mortality, severe complications or 6‐month mortality. Conclusions In this population of gastric cancer surgical patients, the prevalence of sarcopenia was 57.7%, which is high compared to other abdominal surgical oncology populations. However, sarcopenia was not associated with postoperative morbidity or mortality. J. Surg. Oncol. 2015; 112:403–407. © 2015 Wiley Periodicals, Inc.